Fair Value Measurements and Earnings Forecasts Accuracy: Evidence for Romanian Listed Companies - Mihaela Ionascu (Journal of Accounting and Management Information Systems (JAMIS), 2012)
The purpose of this paper is to explore the effect of the use of fair value on analysts' forecasts accuracy for companies listed on Bucharest Stock Exchange (BSE). As the ongoing debates in the international accounting literature tend to favor fare value against the historical cost and conservatism model, we focus on the impact of the measures of these competing accounting behaviors. Based on a sample of 266 firm-month observations (predictions made in 2008 for 2009 and 2010), the paper shows that, for Romanian listed companies, forecast errors for earnings per share reported under local GAAP are positively correlated with a conservative approach and negatively associated with fair value based accounting policies.
Keywords: M41; G17; 650; analysts' forecast accuracy; accounting policies; conservatism; fair value